2021
DOI: 10.35957/jatisi.v8i3.1069
|View full text |Cite
|
Sign up to set email alerts
|

Sistem Pakar Pemilihan Minat Program Studi Menggunakan Metode Forward Chaining

Abstract: Pemilihan program studi kuliah  membuat pelajar menjadi bingung, karena belum memahami potensi diri sendiri sehingga membuatnya berfikir takut salah memilih jurusan program studi. Pada kenyataannya keputusan yang diambil dalam memilih program studi menjadi masalah, mulai dari mengikuti teman atau atas dasar paksaan orang tua. Pemilihan program studi benar-benar harus diperhatikan dan disesuaikan agar tidak menjadi penyesalan untuk kedepannya. Maka dari itu dibuatlah sistem pakar untuk memudahkan pelajar yang i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…An expert system is a system that tries to match human knowledge with computers, where this system is designed to model problem-solving abilities like an expert [1]- [3]. Expert systems can be used to facilitate the selection of majors in tertiary institutions and can provide solutions to users [2], [4]- [5]. Expert systems can be used to assist students in determining the majors to be taken without having to meet experts directly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An expert system is a system that tries to match human knowledge with computers, where this system is designed to model problem-solving abilities like an expert [1]- [3]. Expert systems can be used to facilitate the selection of majors in tertiary institutions and can provide solutions to users [2], [4]- [5]. Expert systems can be used to assist students in determining the majors to be taken without having to meet experts directly.…”
Section: Introductionmentioning
confidence: 99%
“…Here are some previous studies on expert systems using the forward chaining method, namely research conducted by Syihab in 2021, namely the expert system for selecting interest in study programs, obtaining results that the expert system can be used to facilitate the selection of majors in universities based on previous interests and education [4], Then research conducted by Mulyani et al in 2018, namely an expert system to determine lecture majors based on the interests and talents of high school students, obtained the result that the expert system can be used to determine majors based on interests and talents [2], and research conducted by Yayang et al in 2022, namely an expert system to recommend college majors, found that the expert system can be used to provide department recommendations based on the type of interests and talents possessed [9].…”
Section: Introductionmentioning
confidence: 99%